2020
DOI: 10.1002/cbdv.202000328
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Docking, and Biological Evaluation of New Emodin Anthraquinone Derivatives as Potential Antitumor Substances

Abstract: The emodin anthraquinone derivatives are generally used in traditional Chinese medicine due to their various pharmacological activities. In the present study, a series of emodin anthraquinone derivatives have been designed and synthesized, among which 1,3‐dihydroxy‐6,8‐dimethoxyanthracene‐9,10‐dione is a natural compound that has been synthesized for the very first time, and 1,3‐dimethoxy‐5,8‐dimethylanthracene‐9,10‐dione is a compound that has never been reported earlier. Interestingly, while total seven of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Moreover, it displayed good apoptosis induction by G0/G1 cell cycle arrest and increased the reaction oxygen species at an intracellular level. 84 In another study, Li et al evaluated S. lycopersici . Associated with D. gemmacea and isolated two new anthraquinone derivatives, alterporriol Y and macrosporin 2-O-α- d -glucopyranoside.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 99%
“…Moreover, it displayed good apoptosis induction by G0/G1 cell cycle arrest and increased the reaction oxygen species at an intracellular level. 84 In another study, Li et al evaluated S. lycopersici . Associated with D. gemmacea and isolated two new anthraquinone derivatives, alterporriol Y and macrosporin 2-O-α- d -glucopyranoside.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 99%
“…The binding of 1,3-dimethoxy-5,8-dimethyltracene-9,10-dione with the BSA protein has also been extensively studied. Therefore, this research suggested the neuraminidase inhibitory effect and antitumor activity of the novel emodin anthraquinone derivatives [181]. A novel series of emodin derivatives was contrived and assessed for their in vitro proliferative effect.…”
Section: Anticancer and Antiproliferative Activitiesmentioning
confidence: 99%
“…The most recent research results indicate that emodin regulates cell cycle in non-small lung cancer (NSCLC) through hyaluronan synthase 2 (HA2)-HA-CD44/receptor for the hyaluronic acid-mediated motility (RHAMM) interaction-dependent signaling pathway [38]. Li et al [39] synthesized new emodin derivatives, which were further tested for antitumor activity against HCT116 cancer cells.…”
Section: Proliferationmentioning
confidence: 99%